SOSIALISASI DAN VAKSINASI COVID 19 SERTA PENCEGAHANNYA KEPADA WARGA GEREJA BETHEL INDONESIA TABGHA BATAM - Pranada Pane; Steven; Johannes Hutabarat (JURNAL BEATITUDES, 2022)
In all cases, we need to socialize something that we want to do because with the socialization what is our goal, it will be known, understood and even biased to the point of being accepted by the community, especially people who are indeed our targets for carrying out an activity. Socializing about vaccines is also something that is considered necessary and even very important considering the current COVID-19 pandemic. Socializing about vaccines must start from providing an explanation of the vaccine and also the type and then what is its use, it must be admitted that it is not easy to do it but still must be socialized until the community understands and is willing to carry out vaccination. The Bethel Church of Indonesia, the Tabgha congregation, having its address at the Centre Park Complex Block III number 3 Simpang Kara Batam Center, also took part in the implementation of vaccinations for the congregation and the surrounding community. This is done to assist the central and regional governments in carrying out vaccinations for every citizen who lives in their respective areas in order to complete this vaccination program which can prevent people from being affected by the COVID-19 virus.